Critical factors in developing knowledge management systems - Sukumaran, Sanath; Syed Mustapha, S.M.F.D.; Chandran, Kanchana (2016)
Over the past several years, we have seen many articles, research and survey findings highlighting the failures in Knowledge Management (KM) implementation in general and KM Systems (KMS) in particular.Clearly, there is a need to examine the state of KM from a broader perspective to determine the viability of prevailing KM frameworks and if the need for a new approach is required. This paper was inspired by the recent findings in the KM Survey 2016 published by Knowledge Management Professional Society (KMPro) on the critical factors contributing to organisational KM success and failures.The authors of this paper revisited the survey findings of KMPro to determine whether the critical success factors do indeed lead to a successful Knowledge Management System.The outcome of this paper is a conceptual framework and a catalogue of KMS functionalities deemed “critical” to boost the success rate of KM Systems in the future.